Synthesis, Biological Activity and Molecular Docking Studies of Novel Sulfonate Derivatives Bearing Salicylaldehyde - Korkmaz, Adem; Bursal, Ercan (Wiley-V C H Verlag Gmbh, 2022)
Enzyme activity alterations have been associated with many metabolism disorders and have crucial roles in the pathogenesis of some diseases. Tyrosinase is a key enzyme in melanin biosynthesis, which is responsible for skin pigmentation to protect the skin from solar radiation. Pancreatic lipase has been considered a key enzyme for the treatment of obesity. Herein, we reported the synthesis and enzyme inhibitions of a series of sulfonates as possible tyrosinase and pancreatic lipase inhibitors. According to the calculated IC50 values, compound 3f (74.1 +/- 11.1 mu M) and compound 3c (86.6 +/- 6.9 mu M) were determined to be the best inhibitors among the synthesized compounds for the tyrosinase and pancreatic lipase enzymes, respectively. The approach yielded at extremely high level by creating very flexible structural domains for the chemically modified groups. The structural characterization of the target molecules was implemented by H-1-NMR, C-13-NMR, and HR-MS analyses. Also, molecular docking studies of the synthesized compounds with tyrosinase and pancreatic lipase enzymes were conducted using AutoDock Vina software. Additionally, the studies of the absorption distribution, metabolism, and excretion (ADME) were performed to uncover the target compounds ' pharmacokinetics, drug similarities, and medicinal properties of the novel sulfonate derivatives bearing salicylaldehyde.
Keywords: enzyme inhibition; tyrosinase; pancreatic lipase; molecular docking; ADME; sulfonate derivatives; Tyrosinase Inhibitors; Enzyme-Inhibition; Schiff-Bases; In-Vitro; Discovery; Potent